INVENTARISASI POTENSI SUMBER DAYA EKOWISATA DI DANAU WAY JEPARA LAMPUNG TIMUR - imam nur muchlas; Agus Setiawan; Gunardi Djoko Winarno; Sugeng Prayitno Harianto (Jurnal Belantara, 2018)
Lake Way Jepara is one of the tourist destinations in East Lampung district that has the potential to be developed. An inventory of potential resources of ecotourism at Lake Way Jepara is done by the method of a survey to analyze and document the ecotourism resources at the site. The result of this research shows that the potential of ecotourism resources reside on the Mainland and in the waters of the Lake, including the potential of the landscape, flora and fauna, amenities and services, accommodation and infrastructure. The Mainland covers landscape view of the street, hallway view arboretum, view of the dam and the beauty of the landscape of the Lake. Resources of flora and fauna include 29 species of trees, 26 wildlife species and 21 species of fish. The available infrastructure includes the main road, the alternative way, path tracking, bridges, parking and irrigation canals. Facilities and services include an Advisory Board, a gazebo, a symbolic monument, the Hall opens and seating. Accommodation available: hotel, camping ground, operational as well as homestay. The spread of ecotourism resources clumped in two zones, so that will make it easier in the planning and development of ecotourism.